Review on Chinese agricultural science and technology research from a low-carbon economy perspective: hotspots, evolution, and frontiers - Jin, Weibo; Wu, Shiping; Zhang, Yi; Zhou, Gang; Xu, Lijie; Xu, Yao (Frontiers in Environmental Science, 2023)
Under the background of global climate change, agricultural science and technology play a vital role in achieving a low-carbon economy and sustainable development. Based on the research data of agricultural science and technology in WOS and CNKI, adopting the bibliometric method, a knowledge graph was drawn using CiteSpace software; this paper analyzed the hotspot distribution, structural relationship, context of evolution process and further compared the difference between China and abroad from 1998 to 2023. The results indicate that existing research is mainly distributed in the three core modules, including agricultural science and technology, industrialization, modern agriculture, low-carbon agriculture, etc. The evolution of the research context includes three stages: the traditional agricultural stage, the current agricultural stage, and the high-quality agricultural stage. The research in China and abroad have both overlaps and differences in knowledge structure, and the differences mainly exist in the concept of low-carbon agriculture, the research perspectives, and the agricultural technology system. To expand the knowledge structure, deepening the research on the evaluation and measurement of agrarian carbon footprint, micro-production entities, and strengthening international agricultural science and technology cooperation are innovative directions for future studies. This article systematically reviews agricultural scientific research from the perspective of a low-carbon economy, providing a reference for the green and low-carbon transformation of agriculture in each country.